2017
DOI: 10.1007/978-3-319-71273-4_16
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Inference of Twitter Users’ Age Based on What They Follow

Abstract: Twitter provides an open and rich source of data for studying human behaviour at scale and is widely used in social and network sciences. However, a major criticism of Twitter data is that demographic information is largely absent. Enhancing Twitter data with user ages would advance our ability to study social network structures, information flows and the spread of contagions. Approaches toward age detection of Twitter users typically focus on specific properties of tweets, e.g., linguistic features, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…Studies on demographics are also worth of note, in particular for those sites (e.g., Twitter) where demographic information is mostly unavailable. Chamberlain et al [50] and Zhang et al [51] successfully inferred users' age based on their interaction on the social media platform. Other studies on enhancing social data with demographic attributes include gender [52], location [53], ethnicity [54], and political affiliation [55].…”
Section: Related Workmentioning
confidence: 99%
“…Studies on demographics are also worth of note, in particular for those sites (e.g., Twitter) where demographic information is mostly unavailable. Chamberlain et al [50] and Zhang et al [51] successfully inferred users' age based on their interaction on the social media platform. Other studies on enhancing social data with demographic attributes include gender [52], location [53], ethnicity [54], and political affiliation [55].…”
Section: Related Workmentioning
confidence: 99%
“…In our case, vertices represent Twitter users and edges represent a follower/followee relationship, and we treat edges as if they were undirected. This is justified because Twitter is predominantly an interest graph [14] and a large body of research has shown that the homophily principle applies to users who express similar interests in social networks [7,21,42]. By treating the graph as undirected we ensure that all users that follow a common account (indicative of an interest) have a maximum path distance of two.…”
Section: User Neural Graph Embeddingsmentioning
confidence: 99%
“…48,59,87,89,91,96 , the user's name 28,86,92 or declarations on other linked social media 95,96 . While three studies created their labeled datasets by using the accounts of famous social media influencers 57 or other unspecified collection of users whose gender is known 28,43 . Of the 24 studies, only 8 reported data availability with most 'by request', only 2 have working links to the whole corpus (SI Table S6).…”
Section: Datasetsmentioning
confidence: 99%
“…We found in those that developed ad hoc methods, 19 studies that sought to predict the Twitter user's age, where 7 predicted only age 32,43,45,52,69,73,74 . All but one of the studies 59 approached the detection of Twitter users' age as automatic classification of predefined age groups.…”
Section: Agementioning
confidence: 99%